Differences in colorectal cancer (CRC) patients who did and did not undergo screening: Results from the 45 and Up Study cohort. (June 2021) - Thompson, Jake; Ng, James; Armstrong, Bruce; Feletto, Eleonora; Ha, Tam
Highlights: We studied characteristics of Australians participating in Faecal Occult Blood Test (FOBT) screening and diagnosed with colorectal cancer (CRC). CRC patients less likely to participate in FOBT screening were: Females who were overweight (25 kg/m 2 ). Those who consumed less than the recommended five servings of vegetables per day. Those who consumed ≤ 14 standard drinks per week (compared to non-drinkers). Those who did not meet physical activity guidelines. Abstract: Background: The Australian National Bowel Cancer Screening Program is a free population-based screening program aiming to identify precancerous lesions and early colorectal cancer using faecal occult blood tests in average-risk Australians. The participation rate in people invited to screening was 42 % in 2017–2018, well below the 56.6 % target level. Increasing screening in high-risk groups; such as those with a subsequent diagnosis of colorectal cancer, will improve the efficiency of the program. Methods: Patients were participants in the Australian 45 and Up (cohort) study; aged 55 or 65 years between May 2006 and June 2008. Patients reported a history of colorectal cancer in their enrolment questionnaire and whether or not they had screened before diagnosis. Demographic, lifestyle, dietary and health related characteristics were compared between those who did and did not participate in screening. Results: 339 participants who self-reported having colorectal cancer were included. Participants who were female, overweight ( ≥ 25 kg/m 2 ), consumed less than the recommended five servings of vegetables per day, consumed ≤ 14 standard drinks per week (compared to non-drinkers) or did not meet physical activity guidelines were significantly less likely to have participated in screening. Conclusion: Considerable investment has been placed in the National Bowel Cancer Screening Program and the focus now is on improving participation. Our study has taken a unique approach to identifying high-risk groups by exploring factors related to screening participation in colorectal cancer patients. These findings can further leverage the program by targeting high-risk populations to reduce the colorectal cancer burden in Australia.